Plinth of the southern shrine in the Triple-shrine Temple - Temples of India Project Team (Jio Institute, 2024)
The plinth of the southern shrine in the Triple-shrine Temple to the northwest of Mahanaleshwar Temple is visible only from the jadya kumbha moulding, which is followed by the kalasha moulding. Above this, there are the kapotali mouldings with gavaksha designs at regular intervals. It is pancharatha (consisting of five projections) in design, consisting of a bhadra (central projection), flanked by two slender pratiratha (intermediary projections) and karnas (corner projections). All these projections are separated by recesses. These recesses are devoid of any ornamentation. The pratirathas have vase and foliage motifs and medallions with mithuna (amorous couples).